4x(в 3 степени)y-6xy(во 2 степени) при х=-1 у=2

+92 голосов
4.3m просмотров

4x(в 3 степени)y-6xy(во 2 степени) при х=-1 у=2


Алгебра (137 баллов) | 4.3m просмотров
Дано ответов: 2
+122 голосов

Ответ:

(4x)^{3} =(4*(-1))^{3}=-64\\ (y-6xy)^{2} =(2-6*(-1)*2)^{2} =100

(162 баллов)
+99

x (в 3 степени) y (во 2 степени)

+112

4x2=-4

+114

извини не поняла((

+114

ок

+124 голосов

Ответ:16

Объяснение:4x^3y-6xy^2

Немного упрощаем 2ху(2х^2-3у)

Подставляем 2×(-1)×2×(2×(-1)^2-3×2=-4×(2-6)=-4×(-4)=16

(66 баллов)
+56

4x3y-6xy2 при х=-1 у=2